Geotechnical properties of gullying in Tomsk Oblast - Leonova, Anna Vladimirovna; Lomakina, K.M.; Dmitrieva, S.A.; Baranova, Anastasia Viktorovna (IOP Publishing, 2016)
The article deals with causes, conditions and factors of gullying in Tomsk Oblast, the case of site Grodnenskaya. A nuclear-power station was planned to be constructed in Closed Administrative Territorial Unit Seversk, which led to geotechnical investigation of the area to study the geological processes developing there. The investigation included reconnaissance traverse of the area, geological and geomorphic descriptions, and sampling. The area and percentage of the territory affected by the geological processes were estimated. As a result, it was proved that the geological processes of the area are conditioned by surface water activity leading to gullying and river erosion, and by both ground water and surface water activity resulting in bog formation. It appears that gullying is caused not only by natural factors but also by technogenic ones.
Keywords: оврагообразование; геологические процессы; грунтовые воды; эрозия; Томская область